Determining the presence of chemicals with suspected endocrine activity in drinking water from the Madrid region (Spain) and assessment of their estrogenic, androgenic and thyroidal activities. (June 2018) - Valcárcel, Y.; Valdehíta, A.; Becerra, E.; López de Alda, M.; Gil, A.; Gorga, M.; Petrovic, M.; Barceló, D.; Navas, J.M.
Abstract: Endocrine disruptors (EDs) are natural or man-made chemicals that can affect the health of organisms by interfering with their normal hormonal functions. Many of these substances can cause their effects at very low doses and, considering the key role played by the endocrine system on development, organisms in early phases of growth (foetal, childhood, puberty) are especially sensitive to the action of EDs. In addition, when combined, they can show additive, antagonistic and synergistic activities. Taking all this into account it is essential to determine the presence of this kind of compounds in drinking water. Thus the main aim of the present study was to monitor the presence of substances with suspected or known endocrine activity in drinking water of the Madrid Region (MR) (Central Spain) and determine possible estrogenic, androgenic, or thyroidal activities. Water samples were collected at different times from a number of supply points that received water from reservoirs or rivers. The sampling point with the highest concentration of the analysed substances (up to 30 compounds) was DW1 (1203 ng L −1 ). This sampling point receives water from a drinking water treatment plant (DWTP) that serves the population from the south of the MR with treated water from the Tajuña River. DW2 was the second point with the highest concentration of the analysed substances (1021 ng L −1 ). DW2 receives water from one of the reservoirs in the north of the MR. The highest daily concentrations detected corresponded to the flame retardant Tris (2-chloroethyl)phosphate (TCEP) (266.55 ng L −1 ) and to the nonylphenol diethoxylate (188.57 ng L −1 ) at points DW1 and DW4, respectively, both of which are supplied with treated river water. None of the water samples exhibited androgenic, oestrogenic, or thyroidal activities in in vitro assays based on cells stably transfected with the receptors of interest and luciferase as reporter gene. These results demonstrate that water quality in the MR is high and does not present a health risk for the population, although the concentrations of some substances justify the need for local authorities to continually monitor the presence of these contaminants in order to implement any corrective measures if necessary. Graphical abstract: Image 1 Highlights: Drinking water samples (5 points 7 days) of the Madrid Region were analysed. Chemicals with suspected endocrine activity were analysed in drinking water. Endocrine activity was assessed in vitro by transactivation assays. Some low chemical concentrations reported but no endocrine activity detected. Although water quality is appropriate, continuous monitoring is advisable.